(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Electric vehicle charging stations are generally composed of AC-to-DC and DC-to-DC converters. Many topologies of converters, used for both on-board and off-board EV chargers, have been proposed by the researchers. The off-board Vienna rectifier EV charger is the focus of our work. This EV charger should be controlled for adjusting the system outputs at desired references. Among several control methods existing in the literature, the voltage-oriented and direct power control techniques are selected to control the Vienna rectifier. The aim of this paper is to present a comparative analysis for an Off-board Vienna rectifier controlled individually by the previous mentioned control techniques in order to charge the battery of an electric vehicle from the national grid. A three constant current values of 60A, 80A, and 100A, are imposed to the EV battery as reference currents using PI controllers. The comparison is based on the waveforms of three-phase grid voltages and currents, battery voltages, state of the charge of the battery, and the elapsed time of simulation. The total harmonic distortion (THD) of one phase of the input current at the case of 100A is measured using the fast Fourier transform tool of Matlab/Simulink software which employed for modeling and performing the simulation.